On alpha-prime and Weakly alpha-prime Submodules (European Journal of Pure and Applied Mathematics, 2018)
We have introduced the notion of $α$-prime and weakly $α$-prime submodules as a generalization of prime submodules. Some basic properties of $α$-prime and weakly $α$-prime submodules are the extension of prime submodules. Finally, after introducing the notion of $α$-prime submodules, we also define and study the concept of $α$-prime ideals in a ring.
Keywords: $α$-prime submodules; weakly $α$-prime submodules; $α$-prime ideals; weakly $α$-prime ideals